TDSF-Based Evaluation of Transformer Interactions with VCB, Cable Length, and Neutral Grounding - Álvarez-Mariño, Casimiro (Universidade de Vigo (Bayona, España), 2025)
This paper presents a TDSF-based evaluation of dielectric severity in transformer windings, focusing on transient overvoltages induced by cable–transformer interactions during vacuum circuit breaker (VCB) closing. Unlike prior approaches limited to terminal voltages, this study investigates the highest both spatial and temporal dielectric stress across all combinations of winding nodes and their reference to ground. A hybrid white–black box transformer model implemented in ATP/EMTP is presented and used for high-frequency transient analysis within the transformer. Three case studies on a 50 MVA single-phase, multi-winding transformer validate the model and assess the impact of cable length and neutral grounding resistance. Results show that certain cable lengths increase dielectric stress due to resonance effects, though without exceeding critical thresholds. In contrast, grounding conditions at the LV terminal significantly affect the vulnerability of the winding neutral point. The findings underscore the effectiveness of TDSF-based evaluation in identifying critical stress locations and supporting insulation coordination strategies.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)